2012
DOI: 10.1021/jm3012992
|View full text |Cite
|
Sign up to set email alerts
|

Increased Selectivity toward Cytoplasmic versus Mitochondrial Ribosome Confers Improved Efficiency of Synthetic Aminoglycosides in Fixing Damaged Genes: A Strategy for Treatment of Genetic Diseases Caused by Nonsense Mutations

Abstract: Compelling evidence is now available that gentamicin and geneticin (G418) can induce mammalian ribosome to suppress disease-causing nonsense mutations and partially restore the expression of functional proteins. However, toxicity and relative lack of efficacy at subtoxic doses limit the use of gentamicin for suppression therapy. Although G418 exhibits strongest activity, it is very cytotoxic even at low doses. We describe here the first systematic development of the novel aminoglycoside (S)-11 exhibiting simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
104
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 40 publications
6
104
0
Order By: Relevance
“…Although no such potency gap for the two derivatives has been documented in wild-type bacterial strains, similar tendency has been reported in A1408G mutant bacteria (23), sharing greater binding site similarity with Leishmania. These results also correlate well with the higher miscoding (38) and premature termination codon suppressing potency reported for G418 over Paromomycin in eukaryotes (39).…”
Section: Discussionsupporting
confidence: 82%
“…Although no such potency gap for the two derivatives has been documented in wild-type bacterial strains, similar tendency has been reported in A1408G mutant bacteria (23), sharing greater binding site similarity with Leishmania. These results also correlate well with the higher miscoding (38) and premature termination codon suppressing potency reported for G418 over Paromomycin in eukaryotes (39).…”
Section: Discussionsupporting
confidence: 82%
“…However, a significant portion of the toxicity associated with aminoglycosides may stem from their ability to also inhibit mitochondrial translation. More recently, further advances in the rational design of these compounds has allowed their toxic effects to be separated from their ability to promote translational readthrough (22). In the current study, new synthetic aminoglycosides specifically developed to further enhance readthrough efficacy while maintaining their improved toxicity profile were evaluated in a series of cell-based and animal models for efficacy, toxicity, and pharmacokinetics ( Figure 1).…”
Section: Clinical Relevancementioning
confidence: 99%
“…5 We have recently demonstrated that the observed significantly decreased prokaryotic ribosome specificity of 2 6 and 3 18 is also linked to their reduced mitochondrial translation inhibition and subsequently to their reduced ototoxic effects than gentamicin and G418. The observed similar impact on bacterial ribosome by the current (6 and 7) and previous leads (2 and 3) therefore suggest that 6 and 7 are perhaps less ototoxic than gentamicin and G418.…”
mentioning
confidence: 99%
“…5 To test the validity of this trend, we examined comparative protein translation inhibition of pseudotrisaccharides 2, 3 and 6, 7 in eukaryotic system, using coupled transcription/translation Comparative in vitro stop codon suppression levels induced by compounds 2 (-△-), 6 (-▲-), and gentamicin (--■ --) (left) and by 3 (-Δ-), 7 (-▲-), and gentamicin (--■ --) (right) in a series of nonsense constructs representing various genetic diseases (shown in parentheses): (A) R3X (USH1), (B) R245X (USH1), (C) Q70X (HS), and (D) G542X (CF). The assays were performed as previously described by us.…”
mentioning
confidence: 99%
See 1 more Smart Citation